Development of TACE Refractoriness Scores in Hepatocellular Carcinoma - Chen, Li; Yu, Chen-Xi; Zhong, Bin-Yan; Zhu, Hai-Dong; Jin, Zhi-Cheng; Zhu, Guang-Yu; Zhang, Qi; Ni, Cai-Fang; Teng, Gao-Jun (Frontiers in Molecular Biosciences, 2021)
Purpose: To identify the independent risk factors for transarterial embolization (TACE) refractoriness and to develop a novel TACE refractoriness score and nomogram for predicting TACE refractoriness in patients with hepatocellular carcinoma (HCC). Methods: Between March 2006 and March 2016, HCC patients who underwent TACE monotherapy as initial treatment at two hospitals formed the study cohort and validation cohort. The criteria of TACE refractoriness followed the Japan Society of Hepatology 2014 version of TACE refractoriness. In the study cohort, the independent risk factors for TACE refractoriness were identified, and TACE refractoriness score and nomogram were then developed. The accuracy of the systems was validated externally in the validation cohort. Results: In total, 113 patients from hospital A formed the study cohort and 122 patients from hospital B formed the validation cohort. In the study cohort, 82.3% of the patients (n = 93) developed TACE refractoriness with a median overall survival (OS) of 540 days (95% CI, 400.8–679.1), and the remaining 20 patients in the TACE-non-refractory group had a median OS of 1257 days (95% CI, 338.8–2175.2) (P = 0.019). The median time for developing TACE refractoriness was 207 days (95% CI, 134.8–279.2), and a median number of 2 TACE procedures were performed after refractoriness developed. The independent risk factors for TACE refractoriness were the number of tumors and bilobular invasion of HCC. TACE refractoriness scores < 3.5 indicated a lower incidence of TACE refractoriness, whereas scores > 3.5 points indicated a higher incidence (P < 0.001). In the validation cohort, 77.9% of the patients (n = 95) developed TACE refractoriness with a median OS of 568 days (95% CI, 416.3–719.7), and a median OS of 1324 days was observed in the TACE-non-refractory group (n = 27; 95% CI, 183.5–2464.5). Conclusions: TACE refractoriness impairs the OS of HCC patients. The number of tumors and bilobular invasion status were independent risk factors for TACE refractoriness. The TACE refractoriness score can be an effective tool and easy approach to predict the risk of TACE refractoriness status.